Human Rights Violations Targeting Christians Addressing the Intensifying Anti-Christian Sentiment in a Global Frame (Belügyi Szemle, 2025)
Aim: This article examines the scope and intensity of human rights violations experienced by Christians and suggests some possible strategies to address the problem. The United Nations has expressed concern at the global increase in acts of intolerance and violence directed towards Christians and other people of faith. Yet despite calls by the United Nations to address this growing human rights crisis, little attention has been devoted to the human rights violations experienced by Christians who encounter discrimination in more nations that any other religious group.Methodology: To conduct this study, a domain-based review of the pertinent literature was conducted. Content from a diverse array of disciplines was reviewed and synthesized to extend knowledge in a specific domain, in this case human rights violations targeting Christians.Findings: Both the prevalence and intensity of human rights violations experienced by Christians has reached record levels. Over the past 14 years, the number of nations in which Christians encounter harassment increased from 107 to 155. Currently, Christians experience harassment in 78 percent of 198 nations and territories across the globe. Similarly, the number of nations where Christians experience high levels of persecution has increased from 53 nations in 2014 to 78 nations in 2024.Value: Christians represent some of the most vulnerable and oppressed people in the world. The data and strategies presented in this article position state and private sector actors with the information they need to address the intensifying anti-Christian sentiment across the globe.